2007
DOI: 10.1016/j.ejcts.2006.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Induction chemotherapy does not increase the operative risk of pneumonectomy!

Abstract: In opposition to previous reports, induction chemotherapy did not significantly jeopardize post-operative outcome following pneumonectomy in our experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 25 publications
3
36
0
Order By: Relevance
“…It suggested that the development of BPF was mainly driven by NCR and NR rather than NC itself, which was consistent with the discoveries from most of the included studies. As some reports indicated, the incidence of BPF even slightly decreased in patients treated with NC (35,37,38,44). However, the pooled OR for NC group appeared an obvious trend towards the increased risk of BPF (OR: 1.857; 95%CI: 0.881-3.911; P = 0.104).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…It suggested that the development of BPF was mainly driven by NCR and NR rather than NC itself, which was consistent with the discoveries from most of the included studies. As some reports indicated, the incidence of BPF even slightly decreased in patients treated with NC (35,37,38,44). However, the pooled OR for NC group appeared an obvious trend towards the increased risk of BPF (OR: 1.857; 95%CI: 0.881-3.911; P = 0.104).…”
Section: Discussionmentioning
confidence: 90%
“…3B). The summarized outcomes integrating 12 available studies (21,26,34,35,37,38,42,(44)(45)(46)(47)50) revealed the higher frequency of BPF occurred in patients treated with NC compared with those without NC (OR: 1.857; 95%CI: 0.881-3.911). However, the current evidences did not show the significant impact of NC on BPF occurrence after lung cancer surgery (P = 0.104).…”
Section: Subgroup Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…One of the roles of the multidisciplinary team is to judge resectability and to determine the optimal surgical procedure based on the collaborative interpretation of imaging findings. While the issue is still under debate, 57 it is generally considered that pneumonectomy should be avoided as much as possible if oncologically appropriate, especially after induction chemoradiotherapy. 52 The multidisciplinary team judges whether pneumonectomy can be avoided in marginal cases, for instance, by safely performing reconstruction of the airway or vessels when a primary tumour or a bulky lymph node exists in the hilum along with N2 disease.…”
Section: Management Of Nsclc With Mediastinal Lymph Node Metastasismentioning
confidence: 99%